PEMBINAAN SISWA BERBAKAT DAN BERPRESTASI DI SMA NEGERI 1 SEMARANG - Arini, Esti Gusti (Universitas Muhammadiyah Surakarta, 2012)
Talented student is student who owns ability more than a student in general. Problem which often happens at school in Indonesia is minim of education to talented student. In accommodating fund channel potency to talented student, State Senior High School 1 of Semarang forms special class to talented student and has achievement. Based on background, this research aims to 1) to descripbe strategy construction of student in State Senior High School 1 of Semarang and to descripbe execution of construction of student in State Senior High School 1 of Semarang. This type of research is qualitative ethnography. This research is executed in State Senior High School 1 of Semarang. Subject research is the principal, teacher, and student. Method data collecting use circumstantial interview, observation, and documentation. Data analysis in this research is ethnography analysis. Test authenticity of data by test credibility, transformabilitiy, and conformabilities of expendabilities. The results are 1) Strategy construction of student based on achievement and talent in State Senior High School 1 of Semarang is model study of subdividing of talented student in class of especially with pleasant study strategy and in construction of talented student and have achievement needed and 2) execution of construction of student based on achievement and talent in State Senior High School 1 of Semarang passes some developments with instruction strategy. Those are, first, study bases on problem. Second is exploiting student environment to obtain learning experience. Thirdly, is group activity. Fourth, is making autodidact activity. Fifth is making learning activity to cooperate with society. Sixth is applying assessment of authentic